Analisa Sistem Administrasi Yang Sehat Dalam Penerapan TSAR (Time Registering Systematik Vedike Hold Arkivering And Reservedeler) Terhadap Manajemen Perawatan Dan Perbaikan Permesinan Kapal - Khamdilah, Ali (Politeknik Bumi Akpelni, 2017)
Achieving good ship operation requires a system that can serve, monitor, control work.Ship management is how to manage, manage, regulate activities on board which covers all aspects of daily ship operations to achieve the destination of the shipping company. The implementation of integrated management such as TSAR (Timeregistering Systematisk Vedli Kehold Arkivering and Reservedeler) is a management system used to get the basics of specific maintenance information, pictures of instructions, use of materials so that it will facilitate the work on target.